Marine-Derived Therapeutics for the Management of Glioblastoma: A Case Series and Comprehensive Review of the Literature - Nishika Karbhari; Simon Khagi (Onco)
Introduction: Glioblastoma is a fatal intracranial neoplasm that is refractory to treatment, with inevitable disease recurrence and progression to death. Marine-derived compounds, including those found in nutraceutical products, may provide therapeutic benefit in the setting of glioblastoma. We present two patient cases whose courses demonstrate a compelling role for marine-derived products in the management of glioblastoma. Cases: Case 1 describes a patient with MGMT promoter unmethylated glioblastoma who went on to complete standard of care chemoradiation along with concurrent use of a majority sea cucumber (MSC) blend known as SeaCare® (SeaCare, Torrington, CT, USA). Her survival of over 2 years significantly exceeds the recognized median survival time of glioblastoma. Case 2 describes a patient with a complicated course who experienced dramatic improvement after the initiation of the MSC blend, with an exceptional survival time of over 4 years post-diagnosis. Discussion: The mechanisms of marine-derived products that underlie these dramatic clinical effects are likely multifaceted but may hinge on the modification of the tumor immune microenvironment and suppression of tumorigenic effects. Specifically, the change in tumor-associated macrophages (TAMs) within the tumor microenvironment is central to this complex interplay. Conclusions: Ultimately, the use of marine products in the treatment of glioblastoma may present a novel and promising therapeutic strategy that warrants further investigation.